Characterization of the stemness potency of isolated from the breast cancer cell lines - Saghar Yousefnia; Kamran Ghaedi; Farzad Seyed Forootan; Mohammad Hossein Nasr Esfahani (Tumor Biology)
Stemness phenotype mammospheres established from cell lines and tissues taken from autopsy can be used to test and to identify the most sensitive drugs for chemotherapy. Therefore, the aim of the present study was isolation and characterization of cancer stem cells derived from MCF7, MDA-MB231, and SKBR3 breast cancer cell lines to demonstrate the stemness phenotypes of mammospheres generated for further their applications in therapeutic approaches. In this study, two luminal subtypes of cell lines, MCF7 and SKBR3 and a basal subtype cell line, MDA-MB-231, were chosen. Mammosphere culturing was implemented for breast cancer stem cells isolation and mammosphere formation efficiency. At the next step, CD44+/CD24– cell ratio, Oct4 and Nanog mRNA levels, proliferation rate, migration rate of mammospheres, and drug resistance (in third passage) were evaluated. In addition, tumorigenicity of mammospheres in the chick embryo model was evaluated and compared through the chick chorioallantoic membrane assay. Among mammospheres formed in all three cell lines, MCF7 had the highest mammosphere formation efficiency. CD24 marker (a differentiation marker for the breast cancer cells) was significantly reduced in the mammospheres generated from MCF7 and SKBR3, during three passages. Also, Oct4 and Nanog transcript levels were significantly higher in all three types of mammospheres, as compared with their cell lines. Proliferation, migration rate, and drug resistance of mammospheres generated from all three cell lines were found to be significantly higher. Tumorigenicity of MCF7 mammospheres was confirmed through tumor size measurement. Also, tumorigenicity of MCF7 and SKBR3 mammospheres was confirmed through more migration from ectoderm to mesoderm and endoderm. We succeeded to establish the technology that can be extended to tissue in the future. We have demonstrated a number of mammospheres can be generated from cell lines. Also, cells with different molecular features showed different stemness phenotypes.